Theories, practices, and pluralism: a pragmatic interpretation of critical social science - Bohman, James (1999)
A hallmark of recent critical social science has been the commitment to methodological and theoretical pluralism. Habermas and others have argued that diverse theoretical and empirical approaches are needed to support informed social criticism. However, an unresolved tension remains in the epistemology of critical social science: the tension between the epistemic advantages of a single comprehensive theoretical framework and those of methodological and theoretical pluralism. By shifting the grounds of the debate in a way suggested by Dewey's pragmatism, the author argues that a thoroughgoing pluralism strengthens, rather than weakens, both the social scientific and political aims of critical social science. Not only does pragmatism offer a plausible interpretation of the epistemic pluralism of the social sciences, but it also provides a way of thinking about their fundamentally practical and political character. With a better normative vocabulary with which to discuss the epistemological issues of such a pluralistic mode of inquiry, the democratic role of critical inquiry and its specifically "practical" form of verification can be clarified. - Reproduced
Keywords: Social sciences